Principal Implementation in Managing Conflict - Olivia R. Mitchell (Tamilis Synex: Multidimensional Collaboration, 2024)
This study tried to describe the principal in managing conflict of the application negative impact of the implementation of the Full Day School. This research was conducted using a qualitative approach with a phenomenological method. These results indicate that the principal can perform a variety of strategies to fix conflict so as not to interfere with the performance of teachers, child's comfort, and confidence of parents